Effecitve leadership for the global economy in the 21ST century - Saee, John (Journal of Business Economics and Management, 2005)
Effective leadership of modern organizations within contemporary global economy in the 21st century is seen as a highly crucial function in organizations and good leadership is the most critical ingredient for successful organizations world over. In this research article, an examination is made of a broad range of theories and conceptualizations of leadership. Differences between managers and leaders are discussed. In addition, the notion of leadership in different cultures is explored which has considerable implications for management of enterprises internationally.First Published Online: 14 Oct 2010